Large-Scale Asset Purchases by Central Banks II: Empirical Evidence - Kerstin Bernoth; Philipp König; Carolin Raab (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Not just since the European Central Bank announced the large-scale purchase of government bonds a few weeks ago, large-scale asset purchases have always been a controversially discussed topic. This DIW Roundup summarizes the measures that have been taken by central banks in Japan, USA and UK and the empirical evidence about the impacts of these measures on financial markets and the real economy.
Keywords: 330